Design Process of Tower Reinforcement Steel Plate at Pinogaluman Lolak Site, North Sulawesi at PT. Krakatau Baja Konstruksi - Agustien, Gina; Ikhsanudin, Ikhsanudin (The Future of Education Journal, 2025)
One of the efforts to overcome the limited service capacity of an existing tower is by adding reinforcements to the tower. With the reinforcement, the desired outcome is for the tower to be able to accommodate additional loads, which may include tower expansion (increasing the height of the tower) and the addition of instruments such as antennas and BTS. This research uses a descriptive research method and a case study at the Product Development and Steel Creative Industry division of PT. Krakatau Baja Konstruksi. The descriptive method is a research method conducted by analyzing existing phenomena and data. The primary data for this research was obtained directly from the field during Industrial Practice at PT. Krakatau Baja Konstruksi, specifically in the Product Development and Steel Creative Industry division. The result of this research is the design or visualization of a Steel Plate in DXF format, which is then transferred to another program or device, namely Cypcut. The Cypcut program will later generate the input for the CNC laser machine, which will be used to produce the Reinforcement Steel Plate for the Pinogaluman Lolak Tower in North Sulawesi.